2015
DOI: 10.3390/rs71215871
|View full text |Cite
|
Sign up to set email alerts
|

Preface: Remote Sensing in Flood Monitoring and Management

Abstract: This Special Issue is a collection of papers studying the use of remote sensing data and methods for flood monitoring and management. The articles contributed span a wide range of topics and present novel processing techniques, review methods and discuss limitations, and also report on current capabilities and outline emerging needs. This preface provides a brief overview of the content.Keywords: flood hazard and risk; satellite imagery; altimetry; digital elevation model; hydrodynamics ScopeFloods can be mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Although the proposed method has lower accuracy than water level sensors, especially when waterlogging is shallow, it is very cheap and could have a wide monitoring coverage. The remote sensing method can monitor urban flooding with wide coverage [9]. However, remote sensing images are usually affected by weather and occlusion, and often have low spatiotemporal resolutions [3,9].…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the proposed method has lower accuracy than water level sensors, especially when waterlogging is shallow, it is very cheap and could have a wide monitoring coverage. The remote sensing method can monitor urban flooding with wide coverage [9]. However, remote sensing images are usually affected by weather and occlusion, and often have low spatiotemporal resolutions [3,9].…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…The remote sensing method can monitor urban flooding with wide coverage [9]. However, remote sensing images are usually affected by weather and occlusion, and often have low spatiotemporal resolutions [3,9]. Compared with the remote sensing method, this proposed method has higher spatiotemporal resolution and accuracy, and it is less prone to be affected by weather and occlusion, but monitoring coverage may be smaller due to the limitation of camera distributions.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Road corridors should be protected by engineered structures such as levees to prevent human and social risks. Instantaneous sea level monitoring by remote sensing and ground sensors are often installed to prevent the flooding risk [104,105].…”
Section: Sea Level Risementioning
confidence: 99%
“…Compared with high spatial resolution sensors, such as optical sensors like the Landsat and radar sensors, which usually offer a 6-16 day repeat cycle, operational satellites usually have relatively high temporal resolution, of twice per day for polar orbiting satellites and 5-30 min for operational geostationary satellites. As a flood is usually a short term event, operational satellites with large area coverage and frequent revisit, either used alone or in combination with other high spatial resolution sensors, or complemented by numerical model simulations, have played significant roles in the detection and monitoring of large floods [18][19][20][21]. For example, Schumann et al [18] demonstrated an application for the May-June 2015 Texas flood disaster using only satellite observations.…”
Section: Introductionmentioning
confidence: 99%